2021
DOI: 10.1177/14614448211019155
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Internet appropriation by older people through technological support services

Abstract: While social support—friends, family, and colleagues—is one of the main sources of encouragement and digital literacy for older people, there is evidence that suggests that they may prefer formal sources of support. This study aims to verify the capacity of technological support services to promote literacy and Internet use by older people in multiple contexts. The participants ( N = 560) were retired adults (over 54) residing in Spain and habitual users of technological support services in four organizational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 51 publications
1
9
0
3
Order By: Relevance
“…In this article, I have sought to further our understanding of the complexity of digital media appropriation among older adults by studying the manifold of relations involved in the different phases of digital media appropriation, and based on this, mapping out the different types of appropriation processes. Studying media appropriation among older adults is highly relevant as access and digital media use become more challenging with older age (Barrantes Cáceres & Cozzubo Chaparro, 2019;Bergström, 2017;Fang et al, 2019;Hargittai & Dobransky, 2017;Lissitsa & Chachashvili-Bolotin, 2015;Olsson et al, 2019;Tirado-Morueta et al, 2021). However, the theoretical framework presented in this study -where the notion of transaction (Dépelteau, 2008;Emirbayer, 1997) is connected to digital media appropriation -can also be used in future research studying other groups of people to further the understanding of media appropriation processes.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…In this article, I have sought to further our understanding of the complexity of digital media appropriation among older adults by studying the manifold of relations involved in the different phases of digital media appropriation, and based on this, mapping out the different types of appropriation processes. Studying media appropriation among older adults is highly relevant as access and digital media use become more challenging with older age (Barrantes Cáceres & Cozzubo Chaparro, 2019;Bergström, 2017;Fang et al, 2019;Hargittai & Dobransky, 2017;Lissitsa & Chachashvili-Bolotin, 2015;Olsson et al, 2019;Tirado-Morueta et al, 2021). However, the theoretical framework presented in this study -where the notion of transaction (Dépelteau, 2008;Emirbayer, 1997) is connected to digital media appropriation -can also be used in future research studying other groups of people to further the understanding of media appropriation processes.…”
Section: Discussionmentioning
confidence: 98%
“…This requires certain experience with and knowledge of digital devices and apps. As stated in the introduction, studies have shown how demographic factors such as younger age facilitate the appropriation of digital devices and applications (Barrantes Cáceres & Cozzubo Chaparro, 2019;Bergström, 2017;Fang et al, 2019;Hargittai & Dobransky, 2017;Lissitsa & Chachashvili-Bolotin, 2015;Olsson et al, 2019;Tirado-Morueta et al, 2021). This could explain why the younger participants in their 70s with a broader online repertoire and a range of (often newer) devices dominated this group.…”
Section: The Typology Related To Interview Participants' Age Gender A...mentioning
confidence: 98%
See 2 more Smart Citations
“…Tal es el caso de dos Proyectos de I+D+i, liderados en la Universidad de Huelva por Ignacio Aguaded y M. Amor Pérez-Rodríguez, sobre Youtubers e Instagrammers (Instatubers, 2021;Yougrammers, 2019), en los que se analiza la competencia mediática de estos prosumidores, así como de los receptores de sus creaciones y las potencialidades de estas redes para afrontar este ecosistema informativo. Estas investigaciones han aportado importantes resultados en torno a los usos y acceso de la población infantil y juvenil (Castillo-Abdul et al, 2020;Lozano-Díaz & Fernández-Prados, 2021;Ramírez-García et al, 2022;, los colectivos en riesgo de exclusión social (Bonilla-del-Río et al, 2022;Civila et al, 2020;Vizcaíno-Verdú & Aguaded, 2022), las personas mayores (Tirado-Morueta et al, 2021), la persuasión política (Jaramillo-Dent et al, 2022a), la inmigración latinoamericana (Jaramillo-Dent et al, 2022b), los educadores y enseñanza , los contenidos tendencia conectados por la música (Vizcaíno-Verdú & Abidin, 2022), divulgadores científicos en redes sociales (Vizcaíno-Verdú et al, 2021), entre otros. El proyecto Horizonte 2020, Transmedia Literacy (2018), cuyo investigador principal es Carlos Scolari, de la Universidad Pompeu Fabra, también ha proporcionado interesantes aportaciones en relación con la identidad digital de los jóvenes y la curación de contenidos (Márquez et al, 2022).…”
Section: Un Campo De Investigación Emergenteunclassified